An economic and financial evaluation of the health benefits of electrification - Delport, Jaco (School of Economics, 2016)
The health benefits of a national household electrification programme are investigated. Cognisance is taken of the lack of utilisation of electricity by newly electrified households. The impact of electrification on air pollution levels and paraffin utilisation is investigated to establish the effect on morbidity due to respiratory infection, paraffln poisoning and bums. The reduced demand for health services stemming from a reduction in morbidity is quantified and its macroeconomic implications investigated. The implications that the results of this quantification process holds for the financing requirements of a national household electrification programme as well as the microeconomic factors underlying the success of such a programme are highlighted. Chapter 1 outlines the methodology that will be used to firstly establish the expected switch to electricity as sole energy-carrier by newly electrified households, secondly to establish the health implications of such a switch, and thirdly to quantify these health implications. Chapter 2 reports the results of the modelling exercise, chapter 3 the resulting health implications and chapter 4 the quantification process. Chapter 5 looks at the macroeconomic implications of the health benefits of electrification. Chapter 6 investigates the impact of the results of this thesis on the financing requirements of the electrification programme. Bibliography: pages 63-68.